Agility, adaptability, and alignment: new capabilities for PSM in a post-pandemic world. Issue 4 (October 2021) - Patrucco, Andrea S.; Kähkönen, Anni-Kaisa
Abstract: Purchasing and Supply Management (PSM) was overwhelmed by a perfect storm during the Covid-19 emergency, in both the public and private sectors. Many organizations were caught unprepared, and it became evident that they did not have the capabilities needed to quickly react and respond to changes caused by the pandemic. This poses the questions of where and how PSM systems should evolve to better contribute to organizational responsiveness to crisis events in the future. In this Editorial, which introduces the "PSM learning from the pandemic: transforming for better crisis management" Notes and Debates special issue, the six contributions included in this issue are discussed. We relate the evidence included in the contribution to three critical capabilities of supply chains in the post-Covid-19 business environment – agility, adaptability, and alignment – and, in this editorial, we discuss how they can be conceptualized from a PSM perspective. From a theoretical perspective, we provide a starting point for future studies that want to focus on how these capabilities can be deployed in PSM, and how they impact the supply network design. From a managerial perspective, these definitions provide preliminary points of discussion on what organizations can do to enhance these capabilities in the future.